SOCIAL RESPONSILITY PROJECT FOR LIVEABLE WORLD AND A SUSTAINABLE DEVELOPMENT: GREEN MARKETING - Ufuk DOĞAN (Fırat University, 2019)
Any source in the environment in which we live is not unlimited and all human live as a consumer from birth to death. While satisfying the needs, occuring during the life of the people, we are getting their consumption chances of future generations. Hence, people throughout his life must be included in the consumption behavior which is the most beneficial to the future generations, lived environment and society. Consumer characterizing this kind of behaviours and attitudes describes as a green consumer. These people carry out their preferences that protect the environment and contaminate the items and services which they purchased. Green marketing is emerged a type of marketing, these scarce resources to be used more effectively and efficiently. In other words, these resources with using to be able to meet the needs and wants of the people can be defined as an approach aimed at sustainability. Green marketing is not a concept that draw attention or promote the environmental characteristics of many products and services. Actually, green marketing is a wide range of activities which can be defined as a product modification, replacement of the production process, change the packaging and advertising. The purpose of this study, the emergence of global issues and people's consumption habits for conducting the perception of social responsibility, seen as a members of community that appears to explain the concept of green marketing businesses they use. The purpose of study is that people is conducting consumption habits considered social responsibility and generated global problems, explaining businesses seen as a members of society using green marketing concept and evaluating marketing mix in terms of green marketing doing literature review about green marketing strategies.